Aktivitas Repelensi dan Insektisidal Beberapa Ekstrak dan Minyak Nabati terhadap Hama Gudang Ephestia cautella - Samsudin Samsudin; Funny Soesanthy; Syafaruddin Syafaruddin (Jurnal Tanaman Industri dan Penyegar, 2016)
Ephestia cautella is one type of storage pests that causes a decrease in cocoa bean quality. Control of this pest using chemical insecticides is not recommended because it is harmful to the environment and consumer health. The research aimed to examine the repellency and insecticidal activity of several types of extract and botanical oil against E. cautella larvae. The research was conducted in the Plant Protection Laboratory, Indonesian Industrial and Beverage Crops Research Institute, from March to November 2012. Botanical materials used were water extracts from Ageratum conyzoides leaves, Azadirachta indica seeds, and Allium sativum tubers, as well as oil from Reutalis trisperma, Syzygium aromaticum, and Andropogon nardus, with respective concentration of 0.5%. The insects test used was the 3rd instar larvae generated in the laboratory. Preliminary testing of the repellency activity was performed used the multiple-choice method, while subsequent testing used the dual-choice method with the parameters of larvae number remains in each treatment until 72 hours. The insecticidal activity was conducted using residual method on the feed substitute, by calculating mortality rate of the test insects. Observations were made at 24, 48, and 72 hours after treatment. The results showed that water extract from A. sativum bulbs and A. conyzoides leaves have high repellency percentage on the  E. cautella larvae, i.e. of 81.33% and 78.67%, respectively. Thus, these two vegetable extracts have the potential to be used as cocoa bean protectant from storage pest attacks. The extracts from A. indica seed, A. sativum bulbs, as well as oil from R. trisperma and S. aromaticum showed insecticidal properties that are able to kill E. cautella larvae.